2007
DOI: 10.1080/10903120701536677
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Transports andNon-Transports in an Urban Emergency Medical Services System

Abstract: In this system, the majority of pediatric patients are not severely ill, and a large number are not transported. Non-transports are more likely to be young adolescents, have been involved in assaults, and have a longer on-scene time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
5
17
0
Order By: Relevance
“…Non-conveyance rates for people who had fallen ranged from 11%–56% [26, 27, 73, 74]. For paediatric patients non-conveyance rates ranged from 13.2%–27.7% [36, 62, 79]. Two studies reported non-conveyance rates for patients with an opioid overdose , ranging from 6.0%–77.0% [44, 54].…”
Section: Resultsmentioning
confidence: 99%
“…Non-conveyance rates for people who had fallen ranged from 11%–56% [26, 27, 73, 74]. For paediatric patients non-conveyance rates ranged from 13.2%–27.7% [36, 62, 79]. Two studies reported non-conveyance rates for patients with an opioid overdose , ranging from 6.0%–77.0% [44, 54].…”
Section: Resultsmentioning
confidence: 99%
“…However, there were no control groups of transported patients in the Moss study. A study specifically examining pediatric patients found that the odds ratio for refusal was highest for assaults, difficulty breathing, and MVCs (22).…”
Section: Discussionmentioning
confidence: 99%
“…8 However, the overall frequency of pediatric ETI is much lower than adults since only 7–13% of EMS transports are for children. 911 …”
Section: Discussionmentioning
confidence: 99%